THE EFFECTS OF SELF-EFFICACY, ISLAMIC HUMAN CAPITAL, AND FINANCIAL LITERACY ON SME PERFORMANCE IN LAMONGAN EAST JAVA, INDONESIA - Anang Kistyanto; Raja Zuraidah Rasi; Jun Surjanti; Tony Seno Aji (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
The fishery sector has made important economic contributions to the island nation of Indonesia. In particular, small- and medium-sized enterprise (SME) fisheries, the owners of which are mostly Muslims with high school educations, have exhibited high self-confidence and effective development. However, the effects of other factors, such as self-efficacy, islamic human capital, and financial literacy, on SME performance have yet to be discussed in detail. Thus, this quantitative study examines the effects of self-efficacy, Islamic human capital and financial literacy on 31 SMEs in Lamongan, East Java. According to the results, self-efficacy had a significant effect on SME performance, whereas both Islamic human capital and financial literacy did not have an impact on such performance.